Sistem Informasi Bursa Kerja Khusus Untuk Penyaluran Kerja Berbasis Web Menggunakan Metode Waterfall pada SMK Global Mulia - Putriani, Puput; Sulaeman, Asep Arwan; Edora, E (LPPM STIKOM Tunas Bangsa, 2024)
Senior High School Global Mulia is one of the schools in Bekasi district. This school is a formal education facility that equips students with knowledge, skills and socialization abilities in society. Therefore, each vocational school has a special agency to handle job placement for graduates, namely the Special Job Exchange (BKK). In this case, the implementation of BKK SMK Global Mulia's duties encountered problems when distributing job vacancy information and job registration information. The job registration process at BKK SMK Global Mulia is still done manually. Based on these problems, this web-based Special Job Exchange Information System is designed for job distribution, managing applicant data and information on calling for selection tests for companies that require it. The system was developed using the waterfall method using the PHP programming language and MySQL database manager. With this special job market information system, it is hoped that it will make it easier for job seekers to obtain more effective information and make it easier for officers to manage BKK.